2014
DOI: 10.1021/la404825g
|View full text |Cite
|
Sign up to set email alerts
|

Role of Asphaltenes in Stabilizing Thin Liquid Emulsion Films

Abstract: Drainage kinetics, thickness, and stability of water-in-oil thin liquid emulsion films obtained from asphaltenes, heavy oil (bitumen), and deasphalted heavy oil (maltenes) diluted in toluene are studied. The results show that asphaltenes stabilize thin organic liquid films at much lower concentrations than maltenes and bitumen. The drainage of thin organic liquid films containing asphaltenes is significantly slower than the drainage of the films containing maltenes and bitumen. The films stabilized by asphalte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
185
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 164 publications
(206 citation statements)
references
References 60 publications
20
185
1
Order By: Relevance
“…These thick lenses indicate the formation of aggregates in the IAA film, which was not observed initially before 30 min aging. These films are similar to asphaltene-in-toluene films as reported by Tchoukov et al 58 They proposed that self-association of asphaltenes is not limited to nanoaggregates but also forms an extended macrostructures in the film with gel-like rheological properties. As indicated by molecular dynamics simulations, such formation and extension of asphaltene network upon aging were believed to be related to hydrogen bonding interactions mainly induced by sulfoxide groups present in IAA.…”
Section: Emulsion Stability and Oil Film Propertiessupporting
confidence: 85%
“…These thick lenses indicate the formation of aggregates in the IAA film, which was not observed initially before 30 min aging. These films are similar to asphaltene-in-toluene films as reported by Tchoukov et al 58 They proposed that self-association of asphaltenes is not limited to nanoaggregates but also forms an extended macrostructures in the film with gel-like rheological properties. As indicated by molecular dynamics simulations, such formation and extension of asphaltene network upon aging were believed to be related to hydrogen bonding interactions mainly induced by sulfoxide groups present in IAA.…”
Section: Emulsion Stability and Oil Film Propertiessupporting
confidence: 85%
“…However, we acknowledge that the adhesion force magnitude for the asphaltene and corresponding bitumen cases is statistically within the experimental error. Although asphaltenes are expected to be the dominant interfacial component, 6,7 the presence of other indigenous species in bitumen may contribute to the overall adhesion between the two interacting interfaces. 50 The "jump-in" adhesion force at the highest asphaltene concentration may be justified by the increased interpenetration of voluminous asphaltene layers.…”
Section: Force Interactions Between Rigid and Deformable Interfacesmentioning
confidence: 99%
“…1 Steric stabilization from the interfacial asphaltene layers and non-uniform drainage of the intervening liquid films, as water droplets are pressed together, lead to enhanced emulsion stability. [5][6][7] The strongly elastic interfacial layers act as a mechanical barrier between water droplets and must be deformed beyond the shear yield strength to initiate droplet coalescence. 4,5,7,8 Although other bitumen components such as resins and naphthenic acids cannot stabilize water-in-oil emulsions alone, they interact with asphaltenes to enhance emulsion stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,4 Asphaltenes and fine bi-wettable solid particles (clays) are known to stabilize such emulsions since they readily partition at the liquid-liquid interface to create mechanical barriers that resist droplet coalescence. [5][6][7][8][9][10][11][12] Recent research has shown that the continual accumulation of asphaltenes at the oil-water interface leads to the formation of elastically-dominated interfacial layers that rupture once a critical yield stress is exceeded. 5,[13][14][15] This yield stress is significantly greater than the typical stress applied during droplet-droplet collision; 16,17 as a result, alternative routes have been explored to reduce the rigidity of these interfacial layers.…”
Section: Introductionmentioning
confidence: 99%